Visualization Proposal for Power System Control Rooms Based on Situational Awareness (2022)
Due to the increasing size of electric power systems and its monitoring and operation needs, people at control rooms face complex situations, analyzing great amounts of information, protocols, operation states, alarms, and control parameters. Additionally, new renewable energy sources data is taking its place nowadays, hindering the process of quickly reading and interpreting information. This is known as the loss of Situational Awareness, SA, of system operators. This work presents proposals for displaying useful information in control rooms and visualization techniques to support accurate SA. Grid data displays, maps, trending graphics, lists, bars graphics, table plots, hierarchical levels, proximity regions, and connections are also proposed and analyzed, presenting an application case in a microgrid control room.